The Effect of the Two Stay Two Stray Cooperative Learning Model on the Mathematical Communication Ability of Junior High School Students - Hendrawan Purba; Elvis Napitupulu (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to (1) find out whether the Two Stay Two Stray learning model influences the mathematical communication skills of class VIII students of SMP Swasta Katolik Budi Murni 2 Medan. The type of research used in this study is a Quasi Experiment or quasi-experiment with the Pretest-Posttest Control Group Design research design. Based on the output, the significance value of 2-tailed Equal variances assumed is 0.035. Where 0.035 <0.05, based on the test criteria, H0 is rejected or accepted Ha, which means that there is an influence of the Two Stay Two Stray cooperative learning model on students' mathematical communication abilities. After that the results of the Mean posttest showed that the Mean posttest for the experimental class was 74.34 while the Mean Posttest for the control class was 68.75, where 74.34 > 68.75. This means that the mathematical communication ability of the experimental class is higher than that of the control class. Based on the research results, it is hoped that teachers can apply the TSTS type cooperative learning model to improve students' mathematical communication skills.